Pembelajaran di Raudatul Athfal (RA) TAUD SAQU Cahaya Hati Halmahera Selatan - Haryati Haryati; Supardi Widodo; Radjiman Ismail; M. Natsir Mahmud (Jurnal Ilmiah Wahana Pendidikan, 2023)
Raudatul Athfal (RA) is an Islamic-based early childhood education unit under the guidance of the Indonesian Ministry of Religion. Al Ghazali's conservative Islamic education is conceptually in accordance with the concept of implementing learning in raudhatul Athfal: First, the Principles of RA Curriculum Development, namely the formation of spiritual and social attitudes, namely behavior that reflects an attitude of faith and piety, development of the nature of faith (religious and moral values), learning that holistic and integrative. Second, in accordance with the characteristics and used as a characteristic of education and learning in RA, which is based on Islamic values ​​based on the Al Quran and Hadith in accordance with Q.S. Annahl/16: 64. These principles and characters are contained in the concept and implementation of learning at RA TAUD SAQU Cahaya Hati South Halmahera as an early childhood education madrasa that uses Al-Quran-based learning. Conservative learning methods used in learning at RA TAUD SAQU Cahaya Hati South Halmahera are a) the model or uswatun hasanah; b) custom or practice; c) Uswatun hasanah/ good example; d) self-reflection or muhasabah and e). Stories and qishah. In the implementation of learning at RA TAUD SAQU Cahaya Hati, it was found that the five methods were applied in the learning process. Consistent application of Islamic values ​​from the time they come to the madrasa to go home. Especially for the Al-Qur'an Thafifz method, the conservative talaqqi, Tasmi, Muraja'ah methods are used and giving prizes to students as a form of encouragement and motivation to enjoy learning and memorizing the Koran